Կորսված ժառանգության նորահայտ էջեր. Երինե գրչուհու ընդօրինակած ձեռագրին կարված պատկերազարդ բացառիկ պատառիկները - Լեյլոյան-Եկմալյան, Աննա; Մանուկյան, Սեդա
While examining guard-leaves, we found illustrated fragments of great interest in manuscript M4088. These guard-leaves which we date to the late ninth or early tenth century, are sewn at the beginning and end of the Lectionary dated to the 17th century. A comparative analysis with the old Lectionaries showed that our miniature is closer to the Paris copy of the Jerusalem Lectionary (Ms P44). These are obviously fragments of a much larger manuscript. The origin of the fragments in question is related to Syunik‘. Many issues of the early period of the miniature art of Syunik‘ are obscured by various circumstances. Alongside natural disasters, perhaps even more catastrophic were the hostile attacks that led to the destruction of a great number of manuscripts. The statistics of the manuscripts which contain illustrated guard-leaves manifests that a considerable number of them were copied in various centres of Syunik‘, especially during the 15th-17th centuries, and probably the fragments of our interest found their way into later manuscripts copied in Syunik‘. Naturally, there were many manuscripts for secondary use at the disposal of Erine and other nuns at Shinuayr Monastery and our Lectionary could be among them. These fragments are unique examples not only of medieval Armenian, but also of world miniature art. They have surprising parallels with the images of the saints of the new church in Tokali (Cappadocia), especially the image of St Claudius (ΚΛΑΥΔΙΟΣ). And a comparative analysis of the images of the prophets and apostles of the Syriac Bible in Paris shows directly the stylistic and iconographic parallels with our fragments. Защитные листы, вшитые в начале и в конце Лекционария XVII века (рукописи M4088) – это иллюстрированные фрагменты, представляющие большой интерес. Их можно датировать концом IX или началом X века. Очевидно, это фрагменты гораздо более крупной рукописи. Сравнительный анализ показал, что рукопись наших листов ближе всего к парижской копии Иерусалимского Лекционария (рук. P44). Вопрос о происхождении этих фрагментов приводит нас в Сюник. Здесь, наряду со стихийными бедствиями, возможно, еще более катастрофическими были вражеские нашествия, приведшие к уничтожению многочисленных рукописей. Не исключено, что именно фрагменты этих уничтоженных рукописей были вторично использованы в более поздних рукописях Сюника. Статистика рукописей с иллюстрированными защитными листами свидетельствует о том, что значительное количество из них было скопировано именно в различных центрах Сюника, особенно в XV-XVII веках. Вероятно, в распоряжении Ерине и других монахинь было много рукописей, хранившихся в монастыре Шинуайр для вторичного употребления, и наш Лекционарий был одним из них. Фрагменты представляют собой уникальные образцы не только средневековой армянской, но и мировой книжной миниатюры. Они обнаруживают удивительные параллели с образами святых новой церкви в Токали (Каппадокия), особенно с образом святого Клавдия (ΚΛΑΥΔΙΟΣ). Сравнительный анализ изображений пророков и апостолов сирийской Библии в Париже также прямо свидетельствует о стилистических и иконографических параллелях с нашими фрагментами.
Keywords: Գրչության արվեստ